Enhancing Residential Safety and Comfort Through Smart Home Security and Automation Technologies - Shahbaz Ali Khan; Shahjahan Samoo; Abdul Salam Shah; Adil Maqsood; Muhammad Adnan Kaim Khani; Asadullah Shah (Journal of ICT, Design, Engineering and Technological Science, 2024)
In the digital era, technology is changing rapidly, and humans are trying to make lives easier, but it brings a new challenge: security. Computer programs or developed hardware can be compromised if not appropriately designed or because of the simple mistakes of an authorized person. The project aims to secure a home using face recognition to unlock the doors and alarm in an emergency. The home security automation technology uses a wireless network to support the alarm and deactivation requirements. The face detection unit uses an internetconnection via an ESP32 CAM; the primary controlled systems are utilized with Wi-Fi technologies. ESP32 manages home electronic appliances and camera devices, featuring a cost-effective structure, easy-to-use interface, and simple deployment. In this project, the system primarily fulfills home security demands using face-detection gadgets, utilizing a controller with a camera. The device can manage a high-power scoring load using security locks.